แนวทางการพัฒนาการบริหารงานประกันคุณภาพภายในสถานศึกษา ด้านกระบวนการบริหารและการจัดการ สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาขอนแก่น เขต 3 - โรจนเดชากูล, สุภาพร; ศิริปุณยนันท์, ธนาศักดิ์; เทียมวงษ์, วีระพงษ์; ภูมิกอง, สมศักดิ์ (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 4 No 2 (2567): พฤษภาคม – สิงหาคม 2567, 2024)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาสภาพปัจจุบัน สภาพที่พึงประสงค์ และความต้องการจำเป็นของการบริหารงานประกันคุณภาพภายในสถานศึกษา ด้านกระบวนการบริหารและการจัดการ สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาขอนแก่น เขต 3 และ2) ศึกษาแนวทางการพัฒนาการบริหารงานประกันคุณภาพภายในสถานศึกษาด้านกระบวนการบริหารและการจัดการ สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาขอนแก่น เขต 3 กลุ่มตัวอย่าง ได้แก่ ผู้บริหารสถานศึกษาและครู จำนวน 291 คน เครื่องมือที่ใช้ในการวิจัย ได้แก่ แบบสอบถาม สถิติที่ใช้นการวิเคราะห์ข้อมูล ได้แก่ ความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และใช้เทคนิค Modified Priority Needs Index (PNI modified ) ผลการวิจัยพบว่า 1) สภาพปัจจุบันของการบริหารงานประกันคุณภาพภายในสถานศึกษาด้านกระบวนการบริหารและการจัดการ สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาขอนแก่น เขต 3 โดยรวมและรายด้านมีค่าเฉลี่ยอยู่ในระดับมาก สภาพที่พึงประสงค์ของการบริหารงานประกันคุณภาพภายในสถานศึกษา ด้านกระบวนการบริหารและการจัดการ โดยรวมและรายด้านมีค่าเฉลี่ยอยู่ในระดับมากที่สุด และความต้องการจำเป็นของการบริหารงานประกันคุณภาพภายในสถานศึกษาด้านการบริหารและการจัดการ เรียงลำดับจากมากไปหาน้อย ได้แก่ ด้านการจัดระบบเทคโนโลยีสารสนเทศเพื่อสนับสนุนการบริหารจัดการและการจัดการเรียนรู้ ด้านการพัฒนาครูและบุคลากรให้มีความเชี่ยวชาญทางวิชาชีพ ด้านการจัดสภาพแวดล้อมทางกายภาพและสังคมที่เอื้อต่อการจัดการเรียนรู้อย่างมีคุณภาพ ด้านการมีระบบบริหารจัดการคุณภาพของสถานศึกษา ด้านการมีเป้าหมาย วิสัยทัศน์และพันธกิจที่สถานศึกษากำหนดชัดเจน และด้านการดำเนินงานพัฒนาวิชาการที่เน้นคุณภาพผู้เรียนรอบด้านตามหลักสูตรสถานศึกษาและทุกกลุ่มเป้าหมาย ตามลำดับ 2) แนวทางการพัฒนาการบริหารงานประกันคุณภาพภายในสถานศึกษาด้านกระบวนการบริหารและการจัดการ สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาขอนแก่น เขต 3 มี 6 ด้าน 18 แนวทาง มีความเหมาะสม ความเป็นไปได้ ในการนำไปใช้เพื่อเป็นแนวทางการพัฒนาพัฒนาการบริหารงานประกันคุณภาพภายในสถานศึกษาด้านกระบวนการบริหารและการจัดการ สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาขอนแก่น เขต 3 อยู่ในระดับมากที่สุดทุกด้าน The objectives of this research were to 1) study the current situation desirable condition and the necessary needs of quality assurance administration within educational institutions. Administrative and management processes under the Office of Khon Kaen Primary Educational Service Area 3 and 2) to study the development of quality assurance administration within educational institutions in terms of administrative and management processes. Under the Office of Khon Kaen Primary Educational Service Area Office 3. The samples were school administrators and teachers a total of 291 people. The research tools were questionnaire. Statistics used in data analysis were frequency, percentage, mean, standard deviation, and Modified Priority Needs Index (PNI modified ) technique was used to prioritize needs. The results were as follows: 1. The current state of quality assurance administration within educational institutions in terms of administrative and management processes. Under the Office of Khon Kaen Primary Educational Service Area, Area 3, overall and each aspect had a high average level. The aspect with the highest average value was the aspect of academic development that emphasized the quality of learners in all aspects according to the curriculum, institutes and all target groups. The desirable condition of quality assurance administration within educational institutions. Administrative and management processes overall and each aspect had the highest average level is the organization of information technology systems to support management and learning management. As for the needs and requirements of quality assurance administration within educational institutes in terms of administration and management in order of descending order, namely, the organization of information technology systems to support management and learning management. The development of teachers and personnel to have professional expertise. The arrangement of physical and social environments conducive to quality learning management. In terms of having a quality management system for educational institutions goal-oriented Clear vision and mission and the implementation of academic development that emphasizes the quality of all-round learners according to the curriculum, institutions and all target groups, respectively. 2) Guidelines for developing quality assurance management within educational institutions in terms of administrative processes and management. Under the jurisdiction of the Khon Kaen Primary Educational Service Area Office, Area 3, there are 6 areas and 18 guidelines that are appropriate. possibility to be used as a guideline for the development of quality assurance management within educational institutions regarding administrative processes and management. Under the Khon Kaen Primary Educational Service Area Office, Area 3 is at the highest level in every aspect.